(Fairtrade) certification: consequences of being a niche market. Issue 2 (2nd April 2020) - Bissinger, Katharina; Leufkens, Daniel
ABSTRACT: Product certification such as organic and fairtrade, leads to a price premium for producers in the majority of cases and thus, also encourages them to increase supplied quantities in order to boost revenue, as empirically evidenced by several studies. Theoretically, this might be a plausible business strategy. The market for certified products is, however, a small one, and producers are not able to sell off the entire quantity produced in the certified niche market. Said supply surplus has to be sold off via conventional trading channels, resulting in a head-on competition between certified and uncertified producers. The analysis at hand sheds light on the revenue gains of certified producers via price discrimination on conventional Southern markets, and the consequences for uncertified producers.